Sustainable coastal living spaces using shipping containers - Savaniu Ioan Mihail; Tonciu Oana; Francu Catalin (E3S Web of Conferences)
The article presents the importance of building coastal living spaces using end-of-life shipping containers - used ship containers - in order to reduce metal waste in coastal areas with a significant impact on greenhouse gas emissions and coastal biodiversity leading to sustainable coastal living spaces. The comparative study between building a house using classical building solutions, reinforced concrete structure and brick masonry, and building the same house using maritime containers attempts to highlight the need to use these containers as coastal living space. The article presents the comparative study between the amount of CO2 emissions generated during the construction of a living space using classical solutions (infrastructure and superstructure in reinforced concrete with masonry) with a useful surface of about 28 square meters and the amount of greenhouse gases generated by the realization of a living space using decommissioned maritime containers with an equivalent useful surface. Following the comparative analysis we found that in the case of using maritime containers we obtain negative values in terms of CO2 emissions compared to the classical construction where the CO2 emissions are much positive.